(untitled) (Eurasian Journal of Humanities and Social Sciences, 2022)
This article describes the views on the Japanese literature of the Nara period (VIII century). As well as, within the framework of the article, there is talk about the unique role and characteristics of the literature of the Nara period in the flourishing of Japanese literature.